EFEKTIVITAS KOMUNIKASI INTERPERSONAL PETUGAS KESEHATAN DENGAN PASIEN TB PARU DALAM MENJAGA KELANGSUNGAN PENGOBATAN DI PUSKESMAS - Henny Yuliastri; Rahmi Widyanti; Sanusi Sanusi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
Interpersonal communication is a process of health workers in interpersonal interactions performed by health workers with pulmonary TB patients in order to maintain continuity of treatment of pulmonary TB patients to complete treatment using verbal and nonverbal communication. Thesis research method is descriptive qualitative research. Where the research was conducted in Teluk Tiram PHC Banjarmasin.The research objective was to determine whether there is influence the quality of interpersonal communication established between health workers with pulmonary TB patients within the continuity of the treatment of diseases in the Gulf oysters PHC Banjarmasin.Results of the study found that the treatment, pulmonary TB patients want the officer to receive and treat them like their own relatives or friends, served with a welcoming and friendly. Pulmonary TB patients want health workers to be honest in giving information and explanations how can they heal. Pulmonary TB patients want health workers to give the award, be friendly, attentive and always giving encouragement. Pulmonary TB patients want health workers to serve them amicably. Most health care workers are already communicating effectively. The implications of effective communication is performed there is a tendency of health workers towards patients treatment is successful.Suggestions of this study to enhance good communication skills for health workers needed special training, should implement a service that is familial and not too formal, spend more time in contact with with pulmonary tuberculosis, truthful information, and can provide encouragement and concern in providing services and foster good communication. Further research needs to be done about that has not been covered in this study.